2016
DOI: 10.1080/03019233.2016.1235371
|View full text |Cite
|
Sign up to set email alerts
|

The effects of strength ratio on the forming limit diagram of tailor-welded blanks

Abstract: In the present study, the influences of strength ratio (SR) are studied on the formability and forming limit diagram (FLD) of tailor-welded blanks (TWBs). AISI 340, St 12 and St 14 steel sheets with equal thickness of 1 mm were used as different kinds of steel to make TWB with different SR. TWBs were obtained by CO 2 laser welding of different steel sheets. Limit strength ratio (LSR) is introduced as a new useful factor to predict the FLD of TWB with different SR. Results of this research show that with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…Outras pesquisas similares, como as desenvolvidas por Riahi et al [21] e por Safdarian [46], deslocaram a linha de solda em relação ao centro do TWB. Constatou-se que, em termos de tração, praticamente não há diferença perceptível entre os resultados.…”
Section: Figuraunclassified
“…Outras pesquisas similares, como as desenvolvidas por Riahi et al [21] e por Safdarian [46], deslocaram a linha de solda em relação ao centro do TWB. Constatou-se que, em termos de tração, praticamente não há diferença perceptível entre os resultados.…”
Section: Figuraunclassified
“…The behavior presented by the rupture load pro le is consistent with that found by [19], which rea rms his theory that the maximum resistance of a TWB does not depend on the weld (as long as it is previously quali ed), and is more related to the materials that make up the plates that give rise to the blank. This goes against what is advocated by [14,21,22].…”
Section: Tensile Testsmentioning
confidence: 68%
“…The authors concluded at the end of the article, that the tensile test shows that the plastic deformation is concentrated in the base material when the weld varies from 30º to 90º, and the stress concentration is in the weld when the weld is at 90º. According to Nalli et al [13], Safdarian [14] and Ahmetoglu et al [15] on the two welded materials there is a balance of forces at work, where Fa = Fb. Therefore, disregarding the metallurgical effects, the threshold can be obtained by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…4) Effects of thickness and strength ration on formability of TWBs were investigated by researchers. [5][6][7] The deformation inhomogeneity in the direction perpendicular to the weld rises with the increase of the thickness ratio, which decreases the formability of the TWB in this direction. Azuma pointed out that when thickness ratio researches TR1.5, the forming height longitudinal and transverse…”
Section: Introductionmentioning
confidence: 99%